Consumer Preferences of Halal-Friendly Hotel Attributes - Fadhila Azhari Shafa (At-Tadbir : jurnal ilmiah manajemen, 2020)
The rapid growth of halal tourism in indonesia has increased the need for tourist destinations to offer halal products as a service to the muslim market. This has an impact on the emergence of an awareness of business actors in indonesia, one of which is a halal-friendly hotel. This study aims to examine consumer preferences for the attributes provided when staying at a halal-friendly hotel. This analysis is confirmatory and uses quantitative methods. Quantitative data collection is done by the survey method through a questionnaire. Research respondents are 107 people with the criteria of those who have stayed at least once at a halal-friendly hotel in DKI Jakarta and Bandung. This analysis was processed using AMOS software version 23. The results of this study are the attributes that can affect consumer preferences in staying at halal-friendly hotels consisting of 4 attributes and 14 indicators namely; (1) halal-friendly service consists of 4 indicators, (2) halal food and beverage consists of 3 indicators, (3) halal-friendly facilities consist of 4 indicators, and (4) halal privacy consists of 3 indicators.